Comparison of Coronary Artery Bypass Grafting and Drug-Eluting Stent Implantation in Patients With Chronic Kidney Disease: A Propensity Score Matching Study - Li, Yang; Hou, XueJian; Liu, TaoShuai; Xu, Shijun; Huang, Zhuhui; Xu, XiaoYu; Dong, Ran (Frontiers in Cardiovascular Medicine, 2022)
Objectives: To compare the long-term outcomes of coronary artery bypass grafting (CABG) versus percutaneous coronary intervention (PCI) with drug-eluting stents (DESs) for coronary artery disease (CAD) patients with chronic kidney disease (CKD). Methods CAD patients with decreased kidney function (estimated glomerular filtration rate <60 ml/min/1.73m2) who underwent CABG (n=533) or PCI with DES (n=952) from 2013 to 2020 were enrolled at a single center. The primary end-point was the composite occurrence of all-cause death. The secondary end-points included MACCEs (defined as death, myocardial infarction, stroke, or any revascularization, myocardial infarction (MI), stroke, or repeat revascularization). Results A total of 1485 patients underwent revascularization, including 533 CABG and 952 PCI patients. The median follow-up duration was 55.6 months (interquartile range 34.3, 74.7 months). Multivariable Cox regression models were used for risk adjustment, and after propensity score matching (PSM), 399 patients were well matched in each group. The 30-day mortality rate in the CABG group was higher than that in the PCI group, but the difference was not statistically significant (5.0% vs 2.5%, p=0.063). At the 1-year follow-up, CABG was associated with higher mortality than PCI [hazard ratio (HR) of 3.72, 95% confidence interval (CI), 1.63–8.49]. At the end of the 5-year follow-up, the PCI group had a higher rate of myocardial infarction (HR of 0.59, 95% CI, 0.38-0.92) and repeated revascularization (HR of 0.54, 95% CI, 0.36- 0.81) than the CABG group. Furthermore, the rate of MACCEs was also higher in the PCI group than in the CABG group (HR of 0.71, 95% CI, 0.55-0.91). CABG had a higher long-term survival rate (68.4% vs 66.0%) but without a statistically significant difference (HR of 1.09, 95% CI, 0.79-1.50) compared to that of PCI. Conclusions Compared to PCI with a drug-eluting stent among patients with CKD, CABG was associated with a lower myocardial infarction rate, repeat revascularization rate and MACCEs during the long-term follow-up. At a follow-up of 1 year, MACCEs and other adverse events were comparable between the two cohorts, but CABG showed increased mortality compared with PCI.